Conjugate heat transfer analysis of bubble growth during flow boiling in a rectangular microchannel. (December 2021) - Lin, Yuhao; Li, Junye; Luo, Yang; Li, Wei; Luo, Xing; Kabelac, Stephan; Cao, Yanlong; Minkowycz, W.J.
Highlights: The conjugate heat transfer in flow boiling simulation plays an important role and cannot be ignored. Various bottom wall materials and thicknesses are analyzed during the bubble growth in microchannel. There exists an optimum thickness for each solid material in the phase-change application. Abstract: The conjugate heat transfer of bubble growth during flow boiling in microchannel has a significant effect on the flow field and heat transfer performance but few studies analyzed it before. In this study, the volume of fluid (VOF) method, Hardt's phase-change model, conjugate heat transfer between solid and fluid domains are adopted within an OpenFOAM solver to investigate the bubble growth and heat transfer performance in a microchannel with changed wall thickness from 5 μm to 160 μm and materials including silicon, aluminum, and copper. The results reveal that even if uniform heat flux is applied to the bottom wall, heat flux is not uniform at the solid-fluid interface due to the phase-change process in the channel. Conjugate heat transfer between the fluid and solid domain plays an important role in transferring the uniform heat flux from the bottom wall to the solid-fluid interface and homogenizing the solid-region temperature distribution, which cannot be ignored in the simulation of the phase-change phenomenon. When using different wall thicknesses, the bubble growth period differs by over two times. An optimum thickness exists for each material because the increasing wall thickness leads to a faster bubble growth rate but higher thermal resistance. With the same bottom wall thickness, the solid material with higher thermal diffusivity owns a faster bubble growth rate, thus a higher heat transfer coefficient. The optimum thickness decreases with increasing thermal diffusivity of the solid-domain material.